2015
DOI: 10.1016/j.scitotenv.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow scarcity on leaf-litter processing under oceanic climate conditions in calcareous streams

Abstract: Although temporary streams represent a high proportion of the total number and length of running waters, historically the study of intermittent streams has received less attention than that of perennial ones. The goal of the present study was to assess the effects of flow cessation on litter decomposition in calcareous streams under oceanic climate conditions. For this, leaf litter of alder was incubated in four streams (S1, S2, S3 and S4) with different flow regimes (S3 and S4 with zero-flow periods) from nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
2
21
0
1
Order By: Relevance
“…, Martínez et al. ), and small, perennial streams experiencing experimental flow reduction (Northington and Webster ). These studies demonstrated that drastic flow decreases generally slowed litter breakdown due to reduced colonization of shredders; and in the absence of surface flow, dissolution and photodegradation became the dominant mechanisms of breakdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Martínez et al. ), and small, perennial streams experiencing experimental flow reduction (Northington and Webster ). These studies demonstrated that drastic flow decreases generally slowed litter breakdown due to reduced colonization of shredders; and in the absence of surface flow, dissolution and photodegradation became the dominant mechanisms of breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Hydraulic stress-discharge relationships are potentially nonlinear and spatially heterogeneous, and are operationally difficult to establish (Kakouei et al 2017), which could limit the success in generalizing the responses of litter breakdown rates to natural hydrologic variations in perennial streams (Turner and Stewardson 2014). In contrast, hydrologic variability has clearer impacts on litter breakdown rates in drought-prone streams experiencing precipitation-induced flow intermittency (Datry et al 2011, Dieter et al 2011, Mart ınez et al 2015, and small, perennial streams experiencing experimental flow reduction (Northington and Webster 2017). These studies demonstrated that drastic flow decreases generally slowed litter breakdown due to reduced colonization of shredders; and in the absence of surface flow, dissolution and photodegradation became the dominant mechanisms of breakdown.…”
Section: Sources Of Variation In Litter Breakdown Ratesmentioning
confidence: 99%
“…These studies have typically been performed under constant conditions. However, actual streams experience natural fluctuations in current, temperature and/or availability of resources, which may profoundly affect the persistence and activity of individual species and their function in the ecosystem (Riedl et al, 2013;Mart ınez et al, 2015). In fact, the functional response of communities to abiotic factor fluctuations may be dependent on the proximity of the functional optimum of the consortium: species that periodically experience their ecological optima may fully play out their ecological function, whereas species exposed to suboptimal conditions may display more reduced performances (Ruel and Ayres, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition of leaf litter in streams is influenced by physico‐chemical variables and biotic communities such as invertebrate shredders (Suberkropp and Chauvet, ; Belančič et al . ; Martínez et al ., ). However, the studied impoundments did not have a significant effect on most physico‐chemical variables, including temperature, nutrients and oxygen concentration, though phosphates and velocity were considerably increased and decreased, respectively, in the sites IU.…”
Section: Discussionmentioning
confidence: 96%